Das Los Judas : über Entstehung und Ziele der Landbeschreibung in Josua 15 - Vos, Jacobus Cornelis de, 1966- (Supplements to Vetus Testamentum,, 2003)
In this book the origin and objects of the land description in Joshua 15 and its context are examined. Town lists and border descriptions are literarily, historiographically and theologically classified against the background of their relationships to Tetrateuch/Pentateuch/Hexateuch and the Deuteronomistic History. The first part deals with the text, context, and literary relationships of Joshua 15. The second part is devoted to the historical-geographical analysis of the area defined by the town list and border description of Joshua 15. In the third part the respective origins and objects of the successive phases in the history of the text are examined. All those who are dealing with Joshua 13-21 and the historiographical and theological meaning of land descriptions should read this thorough and encompassing study